Línea de investigación: etnia y salud (1998)
ABSTRACT: The present article is an attempt to systematize the genesis and development of this line of research. First of all, the background, national and international policies and their own organizations, the context that surrounds the health of the ethnical groups, research background and action are studied, highlighting the education of human talent. Secondly, the conceptual and methodological approach, the object of study, the problematic nuclei and, the hypothesis and the objective of this research are explained. Third, results, finished and – on going researches, tutorial of theses, and publications are also mentioned. Finally, the data on the research group, its international, national and local contacts as well as funding institutions supporting this line of research is also included.